The concept of lita'arofu as a multicultural education model to response religious hate speech - Saibatul Hamdi; Khabib Musthofa (IAIN Salatiga, 2020)
AbstractThe presence of the Religious Hate Speech (RHS) has had negative impacts such as intolerance, extremism, and even radicalism. Given the increasing number of young people, especially students who may be exposed, it is important that prevention efforts are carried out. One of them is through multicultural education. This study aimed to examine the facts of RHS and offer solutions through the concept of lita'arofu (to recognize each other) as a model of multicultural education. The method used is a literature study (library research by conducting a review of relevant literature and previous research. The results of this study indicate that: (1) the phenomenon of RHS in Indonesia is getting worse, as evidenced by cases of hate speech that actually bring down fellow Muslims; (2) multicultural education is urgent to be implemented in schools to create a moderate understanding of religion; (3) development of the interpretation of lita'arofu in QS. Al-Hujurat: 13, among others, changing direction from qabilah to ummah, giving choices instead of imposing, and broadening the perspective The lita'arofu model is important to apply, because this model will present a moderate religious narrative to prevent the RHS from spreading.